2011
DOI: 10.1007/s10763-011-9280-5
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning About Matter in Grade 6 Classrooms: A Conceptual Change Approach

Abstract: The purpose of this study was to enhance the teaching and learning of matter and its properties for grade 6 students. The development of a conceptual change approach instructional unit was undertaken for this purpose. Pre-and post-concept surveys, classroom observations, and student and teacher interviews were used to collect data. The teaching activities not only challenged and encouraged students' conceptual change but also indicated that teachers needed to develop their content knowledge and teaching strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…These results show that concept cartoonbased instruction is more successful in teaching pre-service teachers the more specific reactions in organic chemistry, therefore having more of an effect on conceptual change compared to traditional teaching methods. This draws us to the conclusion that, as some researchers have reported, conceptual change may differ according to content (Tao and Gunstone, 1999;Havu-Nuutinen, 2005;Jonassen et al, 2005;Pımthong et al, 2012). Another important result of our study was that although alternative conceptions showed a decline in the experimental group on the post-test, there was no change in some aspects in the control group (Q.s 7 and 10) and even showed an increase in others (Q.s 9 and 13).…”
Section: Discussionsupporting
confidence: 72%
“…These results show that concept cartoonbased instruction is more successful in teaching pre-service teachers the more specific reactions in organic chemistry, therefore having more of an effect on conceptual change compared to traditional teaching methods. This draws us to the conclusion that, as some researchers have reported, conceptual change may differ according to content (Tao and Gunstone, 1999;Havu-Nuutinen, 2005;Jonassen et al, 2005;Pımthong et al, 2012). Another important result of our study was that although alternative conceptions showed a decline in the experimental group on the post-test, there was no change in some aspects in the control group (Q.s 7 and 10) and even showed an increase in others (Q.s 9 and 13).…”
Section: Discussionsupporting
confidence: 72%
“…This situation shows that promoting conceptual change for some concepts is difficult (Campanario, 2002;Tsaparlis and Papaphotis, 2009). Also, several researchers have stated that the conceptual change process may be context dependent (Tao and Gunstone, 1999;Havu-Nuutinen, 2005;Jonassen et al, 2005;Pımthong et al, 2012). One possible reason for this is that these concepts require the application of prior knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…They transfer the substantial properties and changes to the particle level (García Franco & Taber, 2009;Löfgren & Helldén, 2009). Level 4: Students are able to use a differentiated particle model to explain physical properties and changes of matter Pimthong et al, 2012). They dwell especially on the atom structure and the different interactions between atoms (Adadan, Irving, & Trundle, 2009;Smothers & Goldston, 2010;Stevens et al, 2010;Talanquer, 2009).…”
Section: Physical Properties and Changementioning
confidence: 99%
“…Thus, substances can disappear in chemical reactions and in physical changes (Mohan et al, 2009;Rahayu & Kita, 2010;Smothers & Goldston, 2010). Level 2: Students understand that substances cannot disappear and that the number of particles has to remain constant in chemical reactions or physical changes (Liu & Lesniak, 2006;Pimthong et al, 2012). Students believe that the mass of a substance depends on the position and on the aggregate state of a substance (Othman et al, 2008).…”
Section: Conservationmentioning
confidence: 99%